Research on meso-scale deformation and failure mechanism of fractured rock mass subject to biaxial compression - Xiaoming, Wang; Yuanjie, Xiao; Wenbing, Shi; Juanjuan, Ren; Zhengxing, Chang; Hua, Li (Arabian journal of geosciences, 2021)
Fractured rock masses possess defects that are extensively developed in nature. Studying the deformation and instability process of fractured rock masses is of great significance for an in-depth understanding of the deformation process and instability modes of slopes with fractured rock masses. In this paper, through field survey of fracture distribution statistics and laboratory triaxial compression tests on field-cored rock specimens, the fracture distribution parameters and the basic physical and mechanical parameters of the rock mass were obtained, and a discrete element model of the fractured rock mass based on the representative element volume (REV) size was developed. The meso-scale deformation and failure characteristics of fractured rock masses under different levels of confining pressure were studied. The results show that the deformation process of fractured rock can be divided into fracture closure stage, quasi-elastic stage, unstable stage of new crack initiations, new crack propagation stage, and fracture crack coalescence stage. As the confining pressure increases, the lateral deformation of the fractured rock mass was impeded, and the overall ductility and strength were improved. Further, the failure mode of the fractured rock mass transitioned from overall tensile failure to shear failure, while new cracks were mainly initiated during the quasi-elastic stage of the stress-strain curve due to the bonding failure of the original fracture surface. In essence, the deformation and failure of fractured rock mass are attributable to the initial bonding failure of the original fracture surface, followed by the failure of the rock mass and the subsequent overall instability of the fractured rock mass. From a mesoscopic perspective, the stress-strain response of a fractured rock mass is the macroscopic manifestation of the evolving interaction between internal normal and tangential stress components. The fabric evolution of the fractured rock mass during the deformation process corresponds to distinct deformation stages. The deformation and failure characteristics of the fractured rock mass resemble and indicate those of the slope, and the design parameters of the slope can be calibrated from those of the fractured rock mass. The findings of this paper are of theoretical and practical significance to better understand the deformation and instability process of slopes with fractured rock masses and obtain design parameters of slope stability.